Unusual Length Dependence of the Conductance in Cumulene Molecular Wires. (17th May 2019) - Xu, Wenjun; Leary, Edmund; Hou, Songjun; Sangtarash, Sara; González, M. Teresa; Rubio‐Bollinger, Gabino; Wu, Qingqing; Sadeghi, Hatef; Tejerina, Lara; Christensen, Kirsten E.; Agraït, Nicolás; Higgins, Simon J.; et al.
Abstract: Cumulenes are sometimes described as "metallic" because an infinitely long cumulene would have the band structure of a metal. Herein, we report the single‐molecule conductance of a series of cumulenes and cumulene analogues, where the number of consecutive C=C bonds in the core is n =1, 2, 3, and 5. The [ n ]cumulenes with n =3 and 5 have almost the same conductance, and they are both more conductive than the alkene ( n =1). This is remarkable because molecular conductance normally falls exponentially with length. The conductance of the allene ( n =2) is much lower, because of its twisted geometry. Computational simulations predict a similar trend to the experimental results and indicate that the low conductance of the allene is a general feature of [ n ]cumulenes where n is even. The lack of length dependence in the conductance of [3] and [5]cumulenes is attributed to the strong decrease in the HOMO–LUMO gap with increasing length. Abstract : Cumulen‐Drähte, wie der im Bild gezeigte, mit einer ungeraden Anzahl an Doppelbindungen sind für ihre Länge leitfähiger als erwartet, wie experimentelle Einzelmoleküluntersuchungen mit einem Bruchkontakt und Computersimulationen zeigen. Der Leitwert ist nahezu unabhängig von der Länge, da die HOMO‐LUMO‐Lücke mit zunehmender Moleküllänge stark abnimmt.